(3UhQI Tcd GdCQV aj GdWhd hGdYQVs ((3ESeGYjd Hf eMeO s)
(3ChdgG (B:s
(3bd dG jYde ef ai GdSehGJ hGdCQV GdZjH EdG Gddg Cf CVY dg OGFQg eTJedI Ydi OGFQI GdCQV JhVM eG ETJedJ Ydjg ef GdWhd hGdYQV hGdQaY hGdNaV s
(3BNQgG (B:s
(3hSO Pi GdbQfjf ef HSGda GdCMbGH hjCLhL heCLhL ceG LGA ai fU GdcJGH hHGddg SHMGfg GdEYJUGe hgPg UhQI GdOGFQI GdePchQI aGage Pdc JQTO hGddg Gdehab ddUhGH hZdjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs